The Ancient Arabic Phonetic Lesson and the Position of the Modernists - مذكور نورالدين (Milev Journal of Research and Studies, 2023)
The Arab linguists took precedence in the phonetic studies and this is the testimony of the Westerners themselves because it is related to the Holy Qur’an. And the beginning was with Abi Al-Aswad Al-Du’ali when he set the vowelization of the Holy Qur’an, then Al-Khalil bin Ahmed Al-Farahidi came and described the articulatory system and he talked about the articulation, and he did not use the modern means, then Sibawayh came and differentiated between the letter and the sound; these were the first beginnings to take care of this science, then Ibn Jinni came and spoke about phonology in his two books: (The Secret of Parsing's Industry "Sir Sina'at Al-I'rab") and (The Characteristics "Al-Khasais"). In the modern era, some linguists who studied in the West appeared and were fascinated by Western studies, so they took the position of criticism and denial of the efforts of Arab scholars, and they inserted new issues into their studies and these issues are not from the spirit of Arabic. Our work in this article is to show the originality of this science, and the efforts of Arab linguists in it to invalidate this falsity and establish the truth that our scholars have worked hard, and what they reached was without the use of the means used by the moderns. It became clear that the study of syllables dealt with by the moderns in their studies had nothing to do with Arabic, but rather it is specific to cutting French and English poetry.